2018
DOI: 10.20944/preprints201810.0080.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MISR-GOES 3D Winds: Implications for Future LEO-GEO and LEO-LEO Winds

Abstract: Global wind observations are fundamental for studying weather and climate dynamics. Most wind measurements come from atmospheric motion vectors (AMVs) by tracking the displacement of cloud or water vapor features. These AMVs generally rely on thermal infrared (IR) techniques for their height assignments, which are subject to large uncertainties in the presence of weak or reversed vertical temperature gradients around the planetary boundary layer (PBL) and with tropopause folding. Stereo imaging can overcome th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…This paper draws on our previously published work in stereo winds [10,11] combining low-Earth orbiting (LEO) and GEO imagery and demonstrating stereo winds using the prior (GOES-NOP) generation of GOES satellites. Our methods, explained in Section 2, do not require that the satellite observations be synchronous with each other in time.…”
Section: Introductionmentioning
confidence: 99%
“…This paper draws on our previously published work in stereo winds [10,11] combining low-Earth orbiting (LEO) and GEO imagery and demonstrating stereo winds using the prior (GOES-NOP) generation of GOES satellites. Our methods, explained in Section 2, do not require that the satellite observations be synchronous with each other in time.…”
Section: Introductionmentioning
confidence: 99%
“…The state that minimizes 2 is found iteratively by nonlinear optimization since 2 is mildly nonlinear in . The retrieval process just described was first used in our previous work with MISR-GOES [10] and then with MODIS-GOES stereo winds [11]. A full derivation of the least-squares solution is provided in the Appendix of the MISR-GOES paper.…”
Section: Figurementioning
confidence: 99%
“…This method has been pioneered with MISR [29] and applied in our work in LEO-GEO stereo winds. We use a similar methodology [10] to identify the class of candidate ground-point retrievals by a combination of height above ground level and low speed. Statistics over this class are useful for characterizing retrieval errors even if the problem of tracking a cloud in motion may be different than tracking static terrain as noted by Lonitz and Horvath [30].…”
Section: Ground Point Retrievalsmentioning
confidence: 99%
“…Recent studies have demonstrated that stereo observations from satellite imagers on different geostationary (GEO) and low Earth orbit (LEO) platforms can produce 3D regional AMVs with an accurate height assignment [11][12][13][14][15]. Derived from tracking cloud and moisture features in motion, AMVs have proven to be very valuable for weather forecasts [16,17].…”
Section: Introductionmentioning
confidence: 99%